Table of Content - -, (Journal of Humanities & Social Sciences, 2025)
:Table of Content• Economic Life in the Islamic City during the Mamluk Era in Egypt, Syria, and Palestine (1250-1517): Feudalism, Economic Policies, and the Monetary Inflation CrisisProf. Samir Hassan Al-Chikh Ali• The geomorphology of coastal features between South Sharm and Yanbu in the north to Ras Al-Breika in the south - the western coast of the Kingdom of Saudi Arabia  using remote sensing technologyMs. Maram Hilal Al-Haisuni• Jawad Ali: A Historical Study of His Life, Works, and MethodologyAsst-Lecturer. Jassib Abd Al-Amir Akab, Asst-Prof. Hamid Karimipour• Semiotics of Clothing in the Novel Tawq Al-Hamam: A Reading of Cultural and Social SymbolsCo-Prof. Arwa Dawood Khomayyies• Al-Hilal's victory over Manchester City: an analysis of Western media representations of the event and its symbolic connotationsCo-Prof. Mona Mohammed Ibrahim Al-Sheddi• Contrastive Montage in Examples of Contemporary Saudi PoetryMs. Mona Abdulrahman Alsaeed• Financial Liberalization & Economic Growth: Theoretical OverviewDr. Abubakr Eltigani Elhag
Keywords: The Journal of Human and Social Sciences